Factors related to nutrition knowledge during pregnancy in the working area of susoh community health centre - Riska Maulidanita; Zakiyah Zakiyah (Institute of Computer Science (IOCS), 2023)
Poor maternal nutritional status has been linked to adverse birth outcomes however, the relationship between maternal nutrition and birth outcomes is complex influenced by many factors including age, education, environment and information that vary in different populations. The purpose of this study was to find out about factors related to nutritional knowledge during pregnancy in the working area of the Susoh Health Center. This type of research is analytical with a cross sectional approach, the research was carried out at the Susoh Health Center which was conducted in January 2022. The population in this study is all pregnant women in the Susoh health center working area from January to August 2021 which amounted to 119 people. Accidental sampling sample data collection technique, with questionnaire research instruments using univariate analysis. There is a relationship between age, education, environment and information with nutritional knowledge during pregnancy in the working area of Susoh Community Health Centre.